Strontium-90 Levels in the Diets and Bones of Children. Progress Report - 1967 - Beninson, Dan Jacobo; Ramos, Enrique; Migliori de Beninson, Ambreta; Kramer, J.; Menossi, Carlos Alberto (United States Atomic Energy Commision; Estados Unidos. Health and Safety Laboratory, 1967)
Fil: Beninson, Dan Jacobo Comisión Nacional de Energía Atómica; Argentina